(untitled) (International Journal of Physiotherapy, 2017)
Background: Neck pain is very common. It can negatively affect the patient’s life and may result in disability.This study conducted to compare the effect of different Mulligan techniques which is more effective(Mulligan self-mobilizationorMulligan SNAGs)on cervical position sense, three groups pain and function. Methods: 87subjects with chronic mechanical three groups were randomly assignedtoGroup(1) 29 subjects received Mulligan self-mobilization and traditional treatment.Group(2) 29 subjects received Mulligan SNAGs and traditional treatment. Group(3) 29 subjects received traditional treatment only.Position sense measured by Joint reposition error, pain measured by visual analog scale and function by Functional Neck disability index.Measurements were taken pre and post the intervention period. Results: MANOVA test revealed thatthere was significant improvement in valuesof the post-treatmentin allGroupscompared with pre-treatment of JPE (pre:P=0.725, post:P<0.001), VAS (pre=0.984, post:P<0.001) and NDI (pre=0.903,post:P<0.001). Conclusion: It can be reasoned that both Mulligan self-mobilization and Mulligan SNAGstechniques have a similar effect in JPE, VAS and NDI favoring traditional in chronic mechanical neck pain patients.